The bounds of liberalism : the fragility of freedom - Brown, Neville (Sussex Academic Press, 2014)
The central question at the heart of this consideration is how far the West may need to modify or extend the liberal philosophy that informs its responses to the multiple world crises it is currently addressing. The book provides a review of the strengths and weaknesses of a social liberalism that, broadly speaking, occupies the ground between the moderate Right and the moderate Left, and is founded upon the conviction that the world, in 50 years, will be either considerably better than it is currently or else a good deal worse. This study argues that those concerned with ensuring the former outcome should promote the spread of well-founded democracy among emergent states, without forgetting to look stringently at how well democratic institutions may function in the mass societies of the West. The author applies his expertise in history, international security, planetary development, and applied geophysics in discussing issues such as climate change and resource depletion; community decay, data saturation, democratic devolution, and medical philosophy; and biowarfare, international political economy, and a planetary ethos. He argues that humanity is passing through an evolutionary transition as impacting as that between the Old and the New Stone Ages, and that humankind's perspectives on the immediate future may be honed by free-ranging speculation about what it can anticipate over the next few centuries.